2001
DOI: 10.1179/sic.2001.46.supplement-1.92
|View full text |Cite
|
Sign up to set email alerts
|

Raman microscopy in art history and conservation science

Abstract: Numerous applications of Raman microscopy in art history and conservation science have appeared in the literature, but unfortunately this work has gone largely unrecognized by practitioners in those fields. This article assesses the causes of this situation and seeks to inform conservators, art historians and archaeologists of the role that Raman microscopy is playing in the analysis of historical materials. A brief description of the Raman scattering phenomenon and the instrumentation used to collect Raman sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 115 publications
(192 reference statements)
0
12
0
Order By: Relevance
“…Three measures were taken in each colour area to assure a representative result, and ten to seventy points were analysed in each illumination, according to their size. For most of the pigments, the μ-EDXRF, μ-Raman and FORS allowed an unequivocal characterization and, when necessary, FORS and µ-FTIR were used, as in the case of lakes, its organic additives and binders [8][9][10][11][12][13][14][15][16][17][18][19][20]. Equipment details can be found at the Methods section.…”
Section: Methodsmentioning
confidence: 99%
“…Three measures were taken in each colour area to assure a representative result, and ten to seventy points were analysed in each illumination, according to their size. For most of the pigments, the μ-EDXRF, μ-Raman and FORS allowed an unequivocal characterization and, when necessary, FORS and µ-FTIR were used, as in the case of lakes, its organic additives and binders [8][9][10][11][12][13][14][15][16][17][18][19][20]. Equipment details can be found at the Methods section.…”
Section: Methodsmentioning
confidence: 99%
“…In this contest, Raman spectroscopy is retained as standard non-destructive technique for pigment identification in polychrome artworks, as paintings, sculptures and ancient manuscripts [1][2][3][4][5][6]. The recent research has clearly demonstrated how the method can be highly effective both for the direct in situ analysis of artwork-with the aid of portable and compact devices [3]-and for the in-depth study of micro-samples in the laboratory [4][5][6]. The identification of materials is made even easier by online Raman spectra databases, which are accessible without any restrictions and usable also by non-expert users [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Raman microscopy has perhaps emerged as the most widely used molecular technique for pigment studies [16]. In a similar way to XRF equipment, instrumental developments have led lately to the availability of A-Raman instruments.…”
Section: Painted Work Of Artmentioning
confidence: 99%
“…Advanced analytical methods also allow us to perform authenticity studies or contribute to the development of simple diagnostic techniques necessary for practical applied conservation [1,2]. The analytical methods used in this field of research are identical with those used at the cutting edge of modern science [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Techniques developed for advanced physics, chemistry and biology have a commonality of application to both ancient and modern materials, since problems encountered in both the advanced technology and cultural heritage areas are similar.…”
mentioning
confidence: 99%